Intergenerational class mobility of labour market entrants in Germany and the UK since the 1950s - Trinh, NA; Bukodi, E (Oxford University Press, 2021)
This study examines over-time trends in intergenerational class mobility based on cohorts of labour market entrants in Germany and the UK since the 1950s. We calculate absolute and relative mobility rates, separately for men and women, using the German Socio-Economic Panel (1984–2016), the UK Household Longitudinal Study (2009–2016), and the UK Labour Force Survey (2014–2017). Regarding absolute mobility, we find marked country differences in upward and downward rates. In Germany, downward mobility decreased, while upward mobility rose. In the UK, downward mobility increased, while upward mobility declined. We provide evidence that these differences can be linked to contrasting changes in the distribution of origin and destination classes. Regarding relative mobility, striking country similarities appear. For both countries, we observe increases in social fluidity for respondents entering the labour market during the 1950s and 1960s that cease to continue for cohorts thereafter. Comparisons between adjacent cohorts do not provide evidence that social fluidity follows cyclical developments of the economy or shorter-term volatilities in the labour market.